Visitors’ preferences on seasonal accommodation for the Rainforest World Music Festival / A.R. Mohd Ariffin and Mohd Khairil Naim Mohamed Jamel - Mohd Ariffin, A.R.; Mohamed Jamel, Mohd Khairil Naim (UiTM Press, 2021)
Sarawak Cultural Village (SCV) is an award-winning open-air living museum of Sarawak has been the host to the three days annual Rainforest World Music Festival (RWMF) since 2005. Every year, thousands of visitor flock to SCV grounds to experience the rich Sarawak culture, live performances and celebrations that it offers. Due to its popularity, each year the number of visitors increases with regulars and newcomers. This has created a spike in accommodation demands for the area of Santubong. Unfortunately, the growth of visitors is not supported by adequate desired accommodations within the area. Thus, the objectives of this paper are to identify an ideal seasonal accommodation type and desired basic facilities required during RWMF. Quantitative analysis is incorporated in this research through collection of data gathered from online survey. Set of questionnaires was distributed to the former visitors seeking their views on the seasonal accommodations and facilities preferred. Based on the results of the data collected, it provided some understanding on the seasonal accommodations and facilities that are suitable for RWMF. This finding consequently could help provide a feasible and practical solution towards the spike demand for accommodation facilities during the RWMF.